Penyusunan Lesson Plan Berbasis Multiple intelligences Research (Studi Atas Karya Munif Chatib) - Ulum, M. Nurul (JURNAL PEDAGOGY, 2017)
M. Nurul Ulum. Formulation of Multiple Intelligences Lesson Plan-Based Research Study On Munif Chatib thesis work. 2015. The purpose of this study are: a). Knowing Paradigm Lesson Plan for Multiple Intelligences Based Perspective Chatib Munif. b). To Learn Lesson Plan Concept -Based Research in Multiple Intelligences Perspective Chatib Munif. This study is a qualitative research approach paedagogis psychology. Data collected by one) interview, 2) documentation. The data source of primary data and secondary data analysis ..datadilakukan with inductive and deductive analysis with measures of data reduction, data presentation, and verification concludes. The validity of the data is tested using triangulation techniques, the triangulation of sources, observers, theories, and triangulation methods. Results of the study were 1) Paradigm Lesson Plan Multiple Intelligences Based Research Study on Munif Chatib work. Lesson plan based on Multiple Intelligences Research can change the mindset of how important teachers make creative lesson plan to facilitate teaching and learning. MIR-based lesson plan is very easy and all romantic. 2) the concept of Multiple Intelligences Lesson Plan-Based Research Study on Munif Chatib work. a) Preparation, at this preparatory stage has done things the teacher is to recognize the intelligence of students and prepare lesson plans / lesson plan. (1) Recognizing the intelligence of students, how to recognize the intelligence of these students to perform a test called Multiple Intelligences Research (MIR). (2). The preparation of lesson plans / lesson plan, lesson plans / lesson plans made simple by the teacher to write the book specifically to create lesson plans to prepare learning activities. Aspects of the lesson plans / lesson plan that covers at least KD, indicators, themes, alpha activity zones, sceene setting, learning activities, tools and materials needed learning resources. b) Implementation, at this stage of the implementation of the teachers have been conducting activities to provide apersepsi and motivation to students and has given multiple intelligences based activities to students. (1). Recap and motivation, in this activity the teacher has done the activity of alpha zone and do scenee setting in early learning, and pre-teach and warmer does not always do the teachers at the beginning of learning. (2). Activity-based learning multiple intelligences. c). Assessment, assessment used by teachers in learning multiple intelligences is based authentic assessment to cover three domains, namely; cognitive, affective and psychomotor.